Adsorption of Crystal Violet Dye from Aqueous Solution using Industrial Pepper Seed Spent: Equilibrium, Thermodynamic, and Kinetic Studies - Razia Sulthana; Syed Noeman Taqui; Usman Taqui Syed; T. M. Yunus Khan; Shaik Dawood Abdul Khadar; Imran Mokashi; Kiran Shahapurkar; M. A. Kalam; H. C. Ananda Murthy; Akheel Ahmed Syed (Adsorption Science & Technology)
The economic viability of adsorbing crystal violet (CV) using pepper seed spent (PSS) as a biosorbent in an aqueous solution has been studied. A parametrical investigation was conducted considering parameters like initial concentration of dye, time of contact, pH value, and temperature variation. The analysis of experimental data obtained was carried out by evaluating with the isotherms of Freundlich, Sips, Tempkin, Jovanovic, Brouers–Sotolongo, Toth, Vieth–Sladek, Radke–Prausnitz, Langmuir, and Redlich–Peterson. The adsorption kinetics were studied by implementing the Dumwald-Wagner, Weber-Morris, pseudo-first-order, pseudo-second-order, film diffusion, and Avrami models. The experimental value of adsorption capacity (Qm=129.4 mg g−1) was observed to be quite close to the Jovanovic isotherm adsorption capacity (Qm=82.24 mg g−1) at (R2), coefficient of correlation of 0.945. The data validation was found to conform to that of pseudo-second-order and Avrami kinetic models. The adsorption process was specified as a spontaneous and endothermic process owing to the thermodynamic parametrical values of ΔG0, ΔH0, and ΔS0. The value of ΔH0 is an indicator of the process’s physical nature. The adsorption of CV to the PSS was authenticated from infrared spectroscopy and scanning electron microscopy images. The interactions of the CV-PSS system have been discussed, and the observations noted suggest PSS as a feasible adsorbent to extract CV from an aqueous solution.